Equivalenting of Mathematical Models of Minimum-Phase Systems of High Order in the Class of Nonminimum-Phase - Mokin, V. B.; Mokin, O. B.; Mokin, B. I.; Dovhopoliuk, S. O.; Chernova, I. O. (Visnyk of Vinnytsia Politechnical Institute, 2018)
The method of synthesis of equivalent mathematical models of high-order minimal-phase dynamical systems, which includes measuring systems with complex structure, has been proposed in the class of nonminimum-phase not higher than the second order with the identification algorithm submerged in the frequency domain.